ANALISIS KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SDN 064973 BHAYANGKARA MEDAN - Nadhira Tita An Ni’mah; Dody Feliks Pandimun Ambarita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of students' learning independence, particularly in Indonesian language learning. The purpose of this study was to determine the learning independence of fifth-grade students in Indonesian language learning at SDN 064973 Bhayangkara Medan. This study employed a descriptive qualitative approach with 34 students from classes VA and VB as the research subjects. Data were collected through questionnaires, observations, interviews with homeroom teachers, and documentation. The results showed that students' learning independence was analyzed based on six indicators, namely initiative, responsibility, discipline, self-confidence, self-control, and perseverance. Overall, students' learning independence was categorized as good. A total of 79.41% of students were classified as independent based on the questionnaire results, while the observation results indicated that 58.82% of students were categorized as fairly independent. Students have demonstrated a fairly good foundation of learning independence; however, further improvement is still needed, particularly in the aspects of learning initiative, responsibility, self-confidence, and self-control. Therefore, teachers need to implement more varied learning strategies to enhance.students' learning independence.